Flexible and wireless metasurface coils for knee and elbow MRI - Daniel M. Düx; Robert Kowal; Lucas Knull; Simon Schröer; Othmar Belker; Dominik Horstmann; Moritz Gutt; Holger Maune; Oliver Speck; Frank Wacker; Bennet Hensen; Marcel Gutberlet (European Radiology Experimental)
Abstract Background Metasurface coils (MCs) are a promising magnetic resonance imaging (MRI) technology. Aiming to evaluate the image quality of MCs for knee and elbow imaging, we compared signal-to-noise ratio (SNRs) obtained in standard clinical setups. Methods Knee and elbow MRI routine sequences were applied at 1.5 T, implementing four coil scenarios: (1) 15-channel transmit/receive knee coil; (2) four-channel multipurpose coil (flex coil); (3) MC + spine coil; and (4) MC + multipurpose coil. Three regions of interest (ROIs) at different anatomical depths were compared. Results Seven participants (aged 28 ± 2 years; 6 males) were enrolled. In elbow MRI, the MC + spine coil demonstrated the highest SNR across all ROIs (superficial-anterior: +114%, p = 0.008; middle: +147%, p = 0.008; deep-posterior: +24%, p = 0.039) compared to the flex coil and all ROIs, except the deepest from the MC, compared to the knee coil (superficial-anterior: +28%, p = 0.016; middle: +104%, p = 0.008; deep-posterior: −1%, p = 0.531). In knee MRI, the MC + spine coil provided higher SNR compared to the flex coil, except posterior (superficial-anterior: +69%, p = 0.008; middle: +288%, p = 0.008; deep-posterior: −12%, p = 0.148) versus the knee coil, the MC + spine coil was superior in the middle but non-different in superficial pre-patellar areas and less in deep-posterior areas (superficial-anterior: −8%, p = 0.188; middle: +44%, p = 0.008; deep-posterior: −36%, p = 0.016). Conclusion Wireless MCs exhibited great potential for knee and elbow MRI outperforming the flex coil. Future developments will improve the posterior illumination to increase its clinical value. Relevance statement MCs offer enhanced versatility, flexibility, and patient comfort. If universal MC designs can achieve image quality comparable to those of standard coils and simultaneously be utilized across multiple body areas, the technology may revolutionize future musculoskeletal MRIs. Key Points MCs are promising in MRI, but homogeneity is challenging depending on the design. Signal-to-noise-ratio was improved for knee and elbow imaging with slight inhomogeneous illumination. MCs could match the image quality of standard coils in both knee and elbow imaging. Graphical Abstract